2016
DOI: 10.5578/keg.10628
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Pre-Service Primary School Teachers' Mathematics Teaching Anxiety and Their Beliefs about Teaching and Learning Mathematics

Abstract: ABSTRACT:The purpose of this study was to investigate the relationship between pre-service primary school teachers' mathematics teaching anxiety and their beliefs about teaching and learning mathematics. There were a total of 250 pre-service primary school teachers involved in this study. Of the total, 202 were female and 48 were male pre-service primary school teachers. In the collection of the data, the researchers employed two types of instruments: the Mathematics Teaching Anxiety Scale (MATAS) and the Math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 8 publications
4
14
1
2
Order By: Relevance
“…These results are similar to the results of the study by Başpınar and Peker (2016). In their study on pre-service primary school teachers, Başpınar and Peker (2016) found no significant correlation between traditional beliefs and anxiety about self-confidence, attitude, and pedagogical content knowledge. However, the results of the present study are partially similar to the results of the study by Peker (2016b).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These results are similar to the results of the study by Başpınar and Peker (2016). In their study on pre-service primary school teachers, Başpınar and Peker (2016) found no significant correlation between traditional beliefs and anxiety about self-confidence, attitude, and pedagogical content knowledge. However, the results of the present study are partially similar to the results of the study by Peker (2016b).…”
Section: Discussionsupporting
confidence: 81%
“…In the literature, there is a limited number of studies on the correlation between the components of pre-service teachers' beliefs on math teaching and learning and the components of math teaching anxiety (Peker, 2016b;Başpınar and Peker, 2016). However, whether the components of the beliefs on math teaching and learning have an effect on the components of the anxiety about math teaching or vice versa has not been clearly explained.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations